Comfort in rehabilitation nursing care: Multiple case study - Fialho, Patrícia (2022)
Functioning allows a life with independence and autonomy, Comfort serves as the basis for human development. Objective: to characterize the comfort perception of patients assisted by a specialist in rehabilitation nursing, identify sensitive care outcomes and relevant comfort factors. Method: Multiple case study, descriptive. Twelve patients hospitalized and at home participated in the study, from September 13, 2021 to January 23, 2022. Study approved by the ethics committee, carried out within the scope of Master's in Nursing. Instruments: Functional Independence Measure Mini-Mental State Examination Holistic Comfort Scale – Chronically Ill (HCQ-PT-DC). Results Most participants had compromised self-care, eating, personal hygiene and dressing, the results reveal a significant difference (X2F (2)=13,231; p= .001;n=8) between the previous assessment and the 1st assessment (p=.003 ). The perception of comfort was evaluated in 6 participants and re-evaluated in 4, in all cases, there were improvements in one or more of the types of comfort. Conclusion The importance of the initial assessment of Comfort in patients undergoing rehabilitation programs emerges, as it can influence the success of recovery interventions.